DEVELOPMENT OF COUNTER PRESSURE TECHNIQUE FOR PAIN INTENSITY OF DISMINORE IN ADOLESCENT WOMEN - Sutiyono (Jurnal Profesi Bidan Indonesia, 2023)
Background: Menstruation is a normal part of the cyclical process that occurs in healthy women between puberty and the end of the reproductive years (Rahayu, Pertiwi, and Patimah 2017). During menarche (menstruation) there are disturbances in the form of cramps, pain and discomfort. One of menstrual pain in young women is dysmenorrhea (Abarca, 2021). If dysmenorrhea is not treated immediately, it can have a negative impact on women's activities or activities, especially young women. Counter pressure is persistent pressure exerted by a person by pressing a fist or the bottom of the palm against the sacral area. The aim of this research is to develop a counter pressure technique for pain.Methodology : This study is a quantitative study with a pre-experimental design. The design of this study uses a two-group pretest-posttest design that uses a comparison group (control). In this study, the first test (pre-test) allows researchers to examine the changes that occur after the intervention. The sample of this research obtained a sample of 90 female students. Data analysis using a statistical test that can be used is the Wilcoxon test.Results: The Wilcoxon test results for the intervention application group obtained a PValue of 0.000 <0.05, then: Ha was accepted, Ho was rejected, therefore it can be concluded that there is an effect of the counter pressure method on the intensity of dysmenorrhea pain in young women at MA Sultan Agung Ngawen.Conclusion: there is an influence of the technique of developing the counter pressure method on the intensity of dysmenorrhea pain in young women at MA Sultan Agung Ngawen